Anionic polyacrylamide alleviates cadmium inhibition on anaerobic digestion of waste activated sludge - Baowei Zhang; Xiang Tang; Qiuxiang Xu; Changzheng Fan; Yuying Gao; Shuang Li; Mier Wang; Chao Li (Environmental Science and Ecotechnology, 2024)
The uncontrolled discharge of industrial wastewater leads to a significant cadmium (Cd) accumulation in waste activated sludge (WAS), posing a serious threat to the steady operation of the anaerobic digestion (AD) system in wastewater treatment plants (WWTPs). Therefore, developing a viable approach to cope with the adverse effects of high-concentration Cd on the AD system is urgently required. This study aims to investigate the potential of using anionic polyacrylamide (APAM), a commonly used agent in WWTPs, to mitigate the adverse effects of Cd in a toxic amount (i.e., 5.0 mg per g total suspended solids (TSS)) on AD of WAS. The results showed that the effectiveness of higher APAM on Cd toxicity alleviation was less than that of lower APAM at the studied level (i.e., the effectiveness order was 1.5 mg APAM per g TSS > 3.0 mg APAM per g TSS > 6.0 mg APAM per g TSS). The moderate supplement of APAM (i.e., 1.5 mg per g TSS) recovered the accumulative methane yield from 190.5 ± 3.6 to 228.9 ± 4.1 mL per g volatile solids by promoting solubilization, hydrolysis, and acidification processes related to methane production. The application of APAM also increased the abundance of key microbes in the AD system, especially Methanolinea among methanogens and Caldilineaceae among hydrolyzers. Furthermore, APAM facilitated the key enzyme activities involved in AD processes and reduced reactive oxygen species (induced by Cd) production via adsorption/enmeshment of Cd by APAM. These findings demonstrate the feasibility of using moderate APAM to mitigate Cd toxicity during AD, providing a promising solution for controlling Cd or other heavy metal toxicity in WWTPs.